A Retrospective Cohort Study to Identify the Risk Factors for Urinary Tract Infection After Office Procedures. Issue 3 (March 2022) - Jackson, Araba A.; Ackerman, Cori; Alesna, Nina; Hicks, Kimiah; Tanner, Jean Paul; Chang, Eric S.; Wyman, Allison M.; Bassaly, Renee; Hidalgo, Ryan J.; Greene, Kristie A.
Abstract : Objective: The objective of this study is to identify the incidence of and risk factors for urinary tract infection (UTI) after office cystoscopy and urodynamic studies (UDS) in a female population. Methods: This was a retrospective cohort study investigating incidence of and risk factors for UTI after office testing. Inclusion criteria included women presenting for either cystoscopy or UDS from September 2019 to February 2020. Modified Poisson regression with robust error variance was used to identify risk factors for UTI after cystoscopy and UDS in a female population. Results: A total of 274 patients met inclusion criteria. One hundred eighty-five patients underwent office cystoscopy. Nine (4.8%) had a postcystoscopy UTI. Significant risk factors for postcystoscopy UTI included recurrent UTI (relative risk, 7.51; 95% confidence interval, 1.66–34.05) and a history of interstitial cystitis (relative risk, 4.56; 95% confidence interval, 1.52–13.73). Of those with recurrent UTI, 13.7% had a postcystoscopy UTI. Among patients with interstitial cystitis, 25% had a postcystoscopy UTI. One hundred ninety-two patients underwent UDS. Ten (5.2%) developed a post-UDS UTI. No risk factors were identified. Conclusions: Patients with recurrent UTI were 7.51 times more likely to develop a UTI after cystoscopy, whereas those with interstitial cystitis were 4.56 times more likely to develop a UTI after cystoscopy. The incidence of UTI after UDS was low overall. Understanding who is at higher risk of postprocedural UTIs may help identify subpopulations that may benefit from prophylactic strategies.